Bedtime dosing of antihypertensive medications: systematic review and consensus statement: International Society of Hypertension position paper endorsed by World Hypertension League and European Society of Hypertension. Issue 10 (12th October 2022) - Stergiou, George; Brunström, Mattias; MacDonald, Thomas; Kyriakoulis, Konstantinos G.; Bursztyn, Michael; Khan, Nadia; Bakris, George; Kollias, Anastasios; Menti, Ariadni; Muntner, Paul; Orias, Marcelo; Poulter, Neil; et al.
Abstract : Antihypertensive drug therapy is one of the most efficient medical interventions for preventing disability and death globally. Most of the evidence supporting its benefits has been derived from outcome trials with morning dosing of medications. Accumulating evidence suggests an adverse prognosis associated with night-time hypertension, nondipping blood pressure (BP) profile and morning BP surge, with increased incidence of cardiovascular events during the first few morning hours. These observations provide justification for complete 24-h BP control as being the primary goal of antihypertensive treatment. Bedtime administration of antihypertensive drugs has also been proposed as a potentially more effective treatment strategy than morning administration. This Position Paper by the International Society of Hypertension reviewed the published evidence on the clinical relevance of the diurnal variation in BP and the timing of antihypertensive drug treatment, aiming to provide consensus recommendations for clinical practice. Eight published outcome hypertension studies involved bedtime dosing of antihypertensive drugs, and all had major methodological and/or other flaws and a high risk of bias in testing the impact of bedtime compared to morning treatment. Three ongoing, well designed, prospective, randomized controlled outcome trials are expected to provide high-quality data on the efficacy and safety of evening or bedtime versus morning drug dosing. Until that information is available, preferred use of bedtime drug dosing of antihypertensive drugs should not be routinely recommended in clinical practice. Complete 24-h control of BP should be targeted using readily available, long-acting antihypertensive medications as monotherapy or combinations administered in a single morning dose. Video Abstract: